Virtual reality instruction in automotive technology education at Renton Technical College - Redman, Douglas Hugh (Kansas State University, 2023)
The purpose of this mixed methods study is to determine if virtual reality (VR) instruction may support learning in community college automotive technical education by measuring learners’ levels of presence and faculty perceptions of learning when using VR instruction. Presence is “the subjective experience of being in one place or environment (the computer-generated environment), even when one is physically situated in another (the actual physical locale)” (Knerr et al., 1998, p. 32). If learner levels of presence are high and faculty perceive learning is occurring, it may indicate VR offers educators a valuable tool that can be used to move learners toward success. Two research questions guided this study. The first was: What are the learners’ levels of presence when using VR in automotive technology instruction? To address this question, learners in an automotive technology program at Renton Technical College taking courses incorporating VR instruction were administered the Witmer et al. (2005) Presence Questionnaire. The second research question was: What are faculty perceptions of learning when using VR in automotive technology instruction? To address this question, faculty were interviewed to capture their perceptions of the learning occurring during VR instruction. This study employed a mixed methods approach. The quantitative portion of this study was non-experimental and descriptive, in which learners enrolled in a community college automotive technology course utilizing VR instruction were surveyed. Additionally, the qualitative portion of the study was comprised of interviews with faculty teaching courses using VR to assess their perceptions of the learning occurring during instruction. Finally, the mixed methods analysis employed a convergent parallel design (Creswell & Plano Clark, 2010). The quantitative and qualitative results were provided in a joint display comparison noting the convergent and divergent findings.
Keywords: Presence; Virtual reality; Automotive; Community college; Learning